Sculpture and architecture conquer space. Examples between the Middle Ages and the Contemporary from the Sculptural Presences workshop. - Maria Chiara Manfredi (Festival dell'Architettura Magazine, 2021)
The 2016 Sculptural Presences Workshop had the common theme of investigating the relationship between architecture and art, and was organized by the University of Parma (coordinated by Carlo Quintelli), the IUAV University of Venice, the University of Bologna, the Polytechnic Institute of Milan, and the La Sapienza University of Rome. Of that theoretical-practical experience – the workshop had as its purpose the design of new museum spaces of the CSAC in relation to specific works of art – this article is a precise account of all the contributions made in various ways by the numerous speakers who attended.